A design of 1 to 4 GHz broadband high‐efficiency power amplifier with two‐way concurrent active load modulation method. Issue 6 (31st March 2021) - You, Fei; Peng, Jun; Li, Chuan; Shen, Ce; He, Songbai
Abstract: Active load modulation and harmonic injection can be used to boost the power amplifier's (PA) efficiency, but these techniques must add a fundamental external source or a harmonic generator. In this paper, a two‐way power amplifier architecture is introduced to extend high‐efficiency operation bandwidth by utilizing concurrent active load modulation with a waveform mapping method. Active load modulation is realized in between the two branches with the aid of independent input amplitude and phase control. Based on a calculated waveform database, high‐efficiency operations for both transistors from 1 to 4 GHz are designed in a self‐defined optimization platform considering waveform distance and input parameters. Finally, this PA is fabricated and measured to offer 41.6 to 45.0 dBm power, 8.2 to 11.7 dB gain, and 56% to 89% drain efficiency from 0.85 to 3.85 GHz.